Patient-reported outcome from minimal invasive surgery compared with conventional open surgery for thoracolumbar fractures of the spine - Girts Murans; Laurynas Meska; Marius Gaurilcikas; Stig Mindedahl Jespersen; Martin Lindberg-Larsen (Brain and Spine, 2024)
Study design: retrospective cohort study of prospectively collected data. Objective: The treatment guidelines for thoracolumbar spinal fractures are controversial although minimally invasive surgery (MIS) is a popular alternative to the traditional open approach (TOA). Limited data exists about outcomes after MIS fracture treatment. The main aim of our study was to evaluate self-reported disability, health-related quality of life, pain, and satisfaction after MIS compared with TOA. Methods: Of 173 patients operated from 2014 to 2018, 64.7% patients completed the Oswestry Disability Index (ODI), the EQ-5D-5L, and a tailored clinical follow-up questionnaire on employment status, pain, activity level, and satisfaction with treatment. Results: Of the 112 patients, 34 had MIS and 78 had TOA. Mean follow-up was 56 months. The two groups were comparable on demographic variables apart from mean age - MIS group was 10 years older. The MIS group had better ODI scores (p = 0.046), but the groups were similar regarding return to work and disability retirement. The EQ-5D-5L index for the MIS were very close (mean −0.033, median +0.049) to the Danish population score, while the TOA showed a greater deviation (mean - 0.125, median −0.040). The MIS used less pain medication than the TOA. Both groups were similarly satisfied with treatment results. Conclusion: Our data indicates that MIS surgery for thoracolumbar spinal fractures can achieve acceptable self-reported outcomes in terms of disability, health-related quality of life, pain, and satisfaction with treatment. However, a randomized controlled trial is needed to determine whether the MIS approach is superior to TOA.